Transmisi tradisi Rentak Kudo sebagai pertahanan budaya pada kawasan adat desa Tarutung Kerinci - Azki, Priazki Hajri; Hendra, Hendra (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2023)
The existence of a tradition can have good implications for the style of a culture. This is also determined from the tradition that is transmitted to the younger generation. The Rentak Kudo Kerinci tradition is upheld by the Kerinci indigenous people and still exists today. However, the swift currents of globalization have also become a threat to this tradition where at present many young people are forgetting the traditions from their regions and this is the strong reason for researchers to conduct this research. This study aims to explore the transmission of the Rentak Kudo tradition performed in the indigenous people of Tarutung Kerinci village. This study uses an ethnographic approach, which is an approach that aims to review the socio-culture of a tradition in an indigenous area. The results obtained from this research are that the transmission process is conducted in three ways, namely through traditional institutions, through implementation, through cultural education and local content in schools. The impact of this transmission process forms a strong culture where the Rentak Kudo dance tradition continues to be increasingly popular and in demand. This process should be used as a reference for other traditional areas in maintaining and maintaining socio-cultural values.